ANALISIS POTENSI PAJAK DAERAH DALAM PENINGKATAN PENDAPATAN ASLI DAERAH DI KOTA BITUNG - Wenur, Gebriany Pirade; Karamoy, Herman; Warongan, Jessy D. L. (ACCOUNTABILITY, 2016)
Economic development requires government and the community to develop and explore the potentials of the region to supporting the better economy in the future. Local Tax is one of regional revenues that has an important role in supporting the implementation of regional development of Bitung. High earnings of local taxes will increase revenue (PAD) so the local government are expected to explore the revenue sources (PAD) in improving Local Revenue (PAD) as to reduce dependence on the central government. This study is aimed to quantify and determine the potential of local taxes in the realization of the projected increase regional revenue in Bitung City. This research uses qualitative method with descriptive approach. Based on research and survey, Bitung City has unexplored local taxes potential by the local government (DIPENDA) to be explore. In 2016 to 2020 local taxes potential revenue has been projected to rising of 25 percent. Keywords: Potential, Local Taxes, Local Revenue (PAD)